Overweight and Blood Pressure in Pre-Pubertal Children: A Longitudinal Study - Alves, Marcelo José; Torres, Wésley [UNESP]; von Ah Morano, Ana Elisa [UNESP]; de Carvalho Filho, Carlos Augusto; Castoldi, Robson Chacon; Christofaro, Diego Giulliano Destro [UNESP]; Casonatto, Juliano; Vanderlei, Luiz Carlos Marques [UNESP]; Fernandes, Rômulo Araújo [UNESP] (Springer Nature, 2024)
Objectives: To analyze the longitudinal relationship between overweight and hypertension in school children. Methods: This cohort study enrolled children 6–8 years of age who were then prospectively followed up over a 24 months period with repeat assessments performed at an interval of 11–13 months. Information on participation in physical education classes in school, sports practice outside of school, and economic status were obtained through questionnaires answered by parents/guardians. The measurement of blood pressure, weight, height, and waist circumference was performed during the serial follow-up visits in school. Results: The proportion of hypertension did not change significantly over the 24 months (7.1% to 8.2%; P = 0.690). However, children with overweight and obesity throughout the period, had a 198% [HR (95% CI) 2.98 (1.40, 6.35)] higher risk of having hypertension diagnosed during follow-up when compared to eutrophic children in the same period. Conclusions: The development trajectory of overweight and obesity in children aged 6–8 years was associated with hypertension.
Keywords: Adiposity; Hypertension; Physical activity; Risk factors